Optimization terms and cost of investment-construction projects by detailing components of objects life cycle using information modeling - Shebek, M.; Dubynka, O.; Oryshchenko, V.; Tugai, A.; Petrenko, D. (Ways to Improve Construction Efficiency, 2019)
The article is aimed at reviewing the content of information modeling of construction and investment projects through the joint application of BIM-technologies (Building Information Modeling - information modeling of buildings) for the full life cycle of a construction project. Using this approach in the implementation of investment and construction projects makes it possible to detail the project for making timely decisions at every stage of the project life cycle, from the concept of the future facility to its operation. Application of information technology modeling of a construction site makes it possible to increase the level of interaction between project participants and improve the organization of joint work between all construction participants. This requires quantitative and qualitative transformations, including the transition to information modeling and in areas related to construction, which contribute more efficient distribution of investments and the formation of an optimal project cost, solving the problems of increasing construction volumes and implementing large-scale infrastructure projects in optimal terms. Optimization of business processes is relevant and requires scientific justification and implementation of the study of information modeling technology in the educational process for a high-quality and professional approach to construction projects in practice.